Design and development of antiviral and antimicrobial filter elements - Sartori, Paula (My University, 2026)
The widespread use of facemasks became a necessity during the COVID-19 pandemic caused by the SARS-CoV-2 virus. Even with the onset of vaccination, the use of masks was recommended for an additional two to ten weeks after achieving global vaccination coverage of 70-90%, due to the emergence of new variants of the virus. Facemasks are typically composed of one or more partially filtering materials, and the World Health Organization recommends a filtration efficiency of at least 95%. An added feature to enhance protection is the incorporation of antimicrobial materials, such as graphene oxide (GO) and silver nanoparticles (AgNPs), which provide additional defense against fluids potentially carrying the SARS-CoV-2 virus. Within this context, this study aimed to develop an antiviral and antimicrobial filter element for application in masks and respirators. Different polyamide 6 (PA6) formulations containing graphene oxide (GO) and silver nanoparticles (AgNPs) were prepared and processed into microfibers by solution blow spinning technique for its use as a filter element in face respirators. The resulting samples were then characterized by field emission gun-scanning electron microscopy (FEG-SEM), energy dispersion spectroscopy (EDS), ultraviolet-visible diffuse reflectance spectroscopy (UV-Vis DRS), water contact angle analysis (WCA), thermogravimetric analysis (TGA), respirability testing, and antibacterial, antiviral and cytotoxicity assays. Microbiological analyses demonstrated antibacterial activity against Escherichia coli and Staphylococcus aureus, with inhibition zones of up to 4.0 mm in disk diffusion assays and growth inhibition in liquid medium assays for the samples containing AgNPs. The samples with GO did not present antibacterial activity and were discontinued. Antiviral tests revealed efficacy against the betacoronavirus MHV-3, achieving up to a 99.9% reduction in viral particles. Additionally, cytotoxicity assays indicated initial cytotoxic effects on days 1 and 2, while some extracts exhibited no cytotoxicity by day 7, suggesting cellular adaptation to the culture medium. In general, the microfibers exhibited good dispersion and uniform AgNPs distribution, a hydrophilic character, and thermal stability, with a maximum weight loss of 2.9% attributed to the water evaporation. The sample produced with a silver nitrate concentration of 10 mmol L-1 (A) showed respirability levels within the expected standards established by technical regulations. Based on the dataset and the simplicity of the microfiber fabrication process, this material demonstrates suitability as a filter element for face respirators, with potential applications not only as a preventive measure in future pandemics but also in other products requiring antibacterial or antiviral performance, such as air-conditioning filters, water filters, hospital textiles, and medical dressings. [resumo fornecido pelo autor]
The widespread use of facemasks became a necessity during the COVID-19 pandemic caused by the SARS-CoV-2 virus. Even with the onset of vaccination, the use of masks was recommended for an additional two to ten weeks after achieving global vaccination coverage of 70-90%, due to the emergence of new variants of the virus. Facemasks are typically composed of one or more partially filtering materials, and the World Health Organization recommends a filtration efficiency of at least 95%. An added feature to enhance protection is the incorporation of antimicrobial materials, such as graphene oxide (GO) and silver nanoparticles (AgNPs), which provide additional defense against fluids potentially carrying the SARS-CoV-2 virus. Within this context, this study aimed to develop an antiviral and antimicrobial filter element for application in masks and respirators. Different polyamide 6 (PA6) formulations containing graphene oxide (GO) and silver nanoparticles (AgNPs) were prepared and processed into microfibers by solution blow spinning technique for its use as a filter element in face respirators. The resulting samples were then characterized by field emission gun-scanning electron microscopy (FEG-SEM), energy dispersion spectroscopy (EDS), ultraviolet-visible diffuse reflectance spectroscopy (UV-Vis DRS), water contact angle analysis (WCA), thermogravimetric analysis (TGA), respirability testing, and antibacterial, antiviral and cytotoxicity assays. Microbiological analyses demonstrated antibacterial activity against Escherichia coli and Staphylococcus aureus, with inhibition zones of up to 4.0 mm in disk diffusion assays and growth inhibition in liquid medium assays for the samples containing AgNPs. The samples with GO did not present antibacterial activity and were discontinued. Antiviral tests revealed efficacy against the betacoronavirus MHV-3, achieving up to a 99.9% reduction in viral particles. Additionally, cytotoxicity assays indicated initial cytotoxic effects on days 1 and 2, while some extracts exhibited no cytotoxicity by day 7, suggesting cellular adaptation to the culture medium. In general, the microfibers exhibited good dispersion and uniform AgNPs distribution, a hydrophilic character, and thermal stability, with a maximum weight loss of 2.9% attributed to the water evaporation. The sample produced with a silver nitrate concentration of 10 mmol L-1 (A) showed respirability levels within the expected standards established by technical regulations. Based on the dataset and the simplicity of the microfiber fabrication process, this material demonstrates suitability as a filter element for face respirators, with potential applications not only as a preventive measure in future pandemics but also in other products requiring antibacterial or antiviral performance, such as air-conditioning filters, water filters, hospital textiles, and medical dressings. [resumo fornecido pelo autor]
Keywords: Nanopartículas; Prata; Grafeno; COVID-19; Nanoparticles; Silver; Graphene; COVID-19